La figure de la passante: une allégorie de la décadence? - de Palacio, Jean (Nordlit, 2012)
The Woman Passer-by, casually met with in modern city streets, and soon lost sight of, belongs to the legacy of Baudelaire. Such a figure, ever on the move, always on the verge of disappearance, must needs be nameless, speechless, and out of reach. She is indeed more soul than body, never implied in any love affair or sexual intercourse. If so, however, either sitting, eating or loving, as is often the case in the poetry of fin-de-siècle writers, she is warped out of her true nature and may become an allegory of Decadence, so much the more when turned into a tigress or she-wolf.